2020
DOI: 10.1186/s13244-020-0841-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of early damage of endometrium after artificial abortion by shear wave elastography

Abstract: Objectives: This study aimed to investigate the application of shear wave elastography (SWE) in the early damage detection through assessing the endometrial elasticity after artificial abortion. Methods: A total of nulliparous women (20-30 years) who received ultrasonography in our hospital were recruited between January 2017 and December 2017. These women were divided into normal control group (NC; n = 65), after once artificial abortion group (AOAA; n = 68), after twice artificial abortion group (ATAA; n = 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
(23 reference statements)
2
2
0
Order By: Relevance
“…We evaluated the mechanical properties of the endometrial layer within the endometrial chamber by performing compression tests. Previously, Jiao et al measured the endometrial elasticity of nulliparous women (20-30 years) who received ultrasonography and found that human endometrium has a stiffness ranging from 10 to 32 kPa [26]. Consistently, our results also revealed that the mechanical strength of the endometrial layer was approximately 18 kPa, and the layer had mechanical properties that were similar to those of soft uterine endometrium (figure 2(D)).…”
Section: Mechanical Characteristics Of the Endometrial Layer Within T...supporting
confidence: 89%
“…We evaluated the mechanical properties of the endometrial layer within the endometrial chamber by performing compression tests. Previously, Jiao et al measured the endometrial elasticity of nulliparous women (20-30 years) who received ultrasonography and found that human endometrium has a stiffness ranging from 10 to 32 kPa [26]. Consistently, our results also revealed that the mechanical strength of the endometrial layer was approximately 18 kPa, and the layer had mechanical properties that were similar to those of soft uterine endometrium (figure 2(D)).…”
Section: Mechanical Characteristics Of the Endometrial Layer Within T...supporting
confidence: 89%
“…Next, we performed compression tests to obtain basic mechanical information about each fabricated endometrial layer. Previously, Jiao et al analyzed the elasticity of endometrium among nonpregnant women (20-30 years) who received abdominal ultrasonography and revealed that normal human endometrium has a stiffness ranging from 10 to 32 kPa [30]. Consistently, our results indicated that the biomechanical properties of each fabricated endometrial layer were slightly varied between 18 kPa and 24 kPa, and the layer had mechanical properties that were similar to those of soft uterine endometrium.…”
Section: Mechanical Characteristics Of the Separately Established Art...supporting
confidence: 81%
“…After reading the full texts of these articles, nine articles that did not include the original data and a control study was excluded. Finally, 13 articles were analyzed (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), and the literature screening process is shown in Figure 1. The specific details of the literature retrieval are shown in Table 1.…”
Section: Literature Screening Process and Retrieval Resultsmentioning
confidence: 99%